2016
DOI: 10.1002/chem.201505050
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Oxazolidin‐2‐ones by Oxidative Coupling of Isonitriles, Phenyl Vinyl Selenone, and Water

Abstract: Reaction of alkyl isocyanides, phenyl vinyl selenone, and water in the presence of a catalytic amount of Cs2 CO3 afforded oxazolidin-2-ones in good yields. This unprecedented heteroannulation process created four chemical bonds in a single operation with the isocyano group acting formally as a polarized double bond and phenyl vinyl selenone as a latent 1,3-dipole. The phenylselenonyl group played a triple role as an electron-withdrawing group to activate the 1,4-addition, a leaving group, and a latent oxidant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(5 citation statements)
references
References 106 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…The intense fragment peak in the mass spectrum at m / z 290.0556 indicated the loss of the N -methyl oxazolidinium ring (Figure S41), which supports the deduced structure of 5 as 3-(2-(6-bromo-2-(2-methylbut-3-en-2-yl)-1 H -indol-3-yl)­ethyl)-3-methyloxazolidin-3-ium (most likely, the chloride salt). This is the first example of an oxazolidinium-containing indole found in Nature, although natural compounds containing an N -substituted oxazolidin-2-one are known …”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The intense fragment peak in the mass spectrum at m / z 290.0556 indicated the loss of the N -methyl oxazolidinium ring (Figure S41), which supports the deduced structure of 5 as 3-(2-(6-bromo-2-(2-methylbut-3-en-2-yl)-1 H -indol-3-yl)­ethyl)-3-methyloxazolidin-3-ium (most likely, the chloride salt). This is the first example of an oxazolidinium-containing indole found in Nature, although natural compounds containing an N -substituted oxazolidin-2-one are known …”
Section: Resultsmentioning
confidence: 96%
“…This is the first example of an oxazolidinium-containing indole found in Nature, although natural compounds containing an Nsubstituted oxazolidin-2-one are known. 39 Flustramine V (6) presented a protonated molecule [M + H] + at m/z 337.0916 in the HRESIMS data, corresponding to the molecular formula C 16 H 21 79 BrN 2 O. The IR spectrum of 6 revealed the presence of NH (3423 cm −1 ) and conjugated carbonyl (1677 cm −1 ) groups.…”
Section: Indole Skeleton and Geminal Methyl Groups At N-1 From Cosy C...mentioning
confidence: 99%
“…In 2016, Zhu reported that alkyl isocyanides react with phenyl vinyl selenone in the presence of 1 equivalent of water and a catalytic amount of Cs 2 CO 3 affording oxazolidin-2-ones in good yields [ 31 ]. In this reaction four new bonds were generated and the phenyl selenenonyl group acted not only as an activating and a leaving group, but also as a latent oxidant.…”
Section: Michael-initiated Ring Closuresmentioning
confidence: 99%
“…Oxazolidinones, which are in the family of carbamates, are important chiral auxiliaries in organic synthesis [ 31 , 32 ] and are also common structural units in drugs [ 33 , 34 ] and agrochemicals [ 35 ]. However, the conventional synthetic methods of 2-oxazolidinones rely on hazardous or expensive reagents such as isocyanides [ 36 ] and phosgene [ 37 ]. Recently, B. Gabriele et al reported an alternative unconventional synthetic method to produce oxazolidinones starting from 2-amino alcohols with CO in ionic liquids [ 38 ].…”
Section: Introductionmentioning
confidence: 99%